In-silico docking analysis of bioactive compounds sourced from Punica granatum peel extract: Approaching a precision solution for ovarian cancer - Swarupa Hatolkar; Aishwarya Patil; Hiramoni Lahkar; Poulomi Chakraborty; Bhagyashree Vinit Gokhale; Aarti Shastri (Journal of Ayurveda and Integrative Medicine, 2025)
Background: The MAPK signalling pathways, particularly those involving EGFR and VEGFR, play a pivotal role in the initiation and progression of ovarian cancer. Inadequate regulation of these pathways may lead to uncontrolled cell proliferation, angiogenesis, and metastasis. Targeting mitogen-activated protein kinases (MAPKs), including the epidermal growth factor receptor (EGFR) and vascular endothelial growth factor receptor (VEGFR), has demonstrated significant potential in restraining cancer cell proliferation and angiogenesis, representing a promising avenue among various therapeutic strategies. Objectives: This manuscript aims to investigate the possibility of Mashi a pomegranate peel extract for ovarian cancer treatment, specifically targeting MAPKs (EGFR and VEGFR). Pomegranate (Punica granatum) is a well-known fruit whose varied portions have been used in traditional medicine for ages. Materials and methods: In silico docking of bioactive compounds extracted from the pomegranate peel extract was done using the Autodock 4.2.6 software. A total of 10 two-dimensional ligands were generated with Pubchem site. The targeted proteins VEGFR, EGFR, MAPK, and MAPK8 were docked with the ligands (Sphondin, Isorhamnetin, Lupinine, Ellagic acid, and Citric acid) which were bioactive ingredients identified from pomegranate peel extract. Results: It was observed that the binding energy of protein MAPK 8, MAPK 14, and VGFR was higher to the ligand at ellagic acid at -8.25kcal/mol, -7.61kcal/mol, and - 5.85kcal/mol respectively. However, EGFR observed to bind with ligand Isorhamnetin at -7.48kcal/mol. Conclusion: The MAPK signalling pathways, specifically involving EGFR and VEGFR, play a crucial role in the initiation and dissemination of ovarian cancer. Dysregulation of these pathways can lead to unrestrained cell proliferation, angiogenesis, and metastasis. Our study revealed favorable binding energy between targeted proteins and ligands. Consequently, we infer that proteins exhibiting robust binding energy with bioactive compounds from pomegranate peel extract may exert regulatory control over the signalling pathways. This implies that EGFR and VEGFR can modulate signals by binding to the bioactive compounds in pomegranate peel extract, thereby regulating the MAPK pathway and ultimately curtailing uncontrolled cell proliferation, angiogenesis, and tumor metastasis. supported by simulation studies results.